Variation in Outpatient Oral Antimicrobial Use Patterns among Canadian Provinces, 2000 to 2010 - Shiona K Glass-Kaastra; Rita Finley; Jim Hutchinson; David M Patrick; Karl Weiss; John Conly (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: The volume and patterns of antimicrobial drug use are key variables to consider when developing guidelines for prescribing, and programs to address stewardship and combat the increasing prevalence of antimicrobial resistant pathogens. Because drug programs are regulated at the provincial level, there is an expectation that antibiotic use may vary among provinces.